2013
DOI: 10.11604/pamj.2013.16.117.3136
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antiretroviral therapy (ART) provision in an early cohort of patients initiating ART in Ghana

Abstract: IntroductionAgainst the background of Ghana's ART program which scaled up rapidly since inception in 2003, the study assessed outcomes of an early cohort of patients initiating ART.MethodsThe study utilized the following methods: a cross-sectional study involving patient interviews using a structured questionnaire, a review of records and a retrospective cohort analysis of adults initiating ART between 2003 and 2008 from four selected clinics.ResultsThe 683 study participants consisted of 464 females (67.9%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…Similar findings of negative immune recovery have been reported among HIV co-infected patients in other African countries [ 42 , 44 ]. However, the sustained increases in the CD4+ cell count among the HIV mono-infected is reflective of a positive immunological outcome to therapy, which is also consistent with a previous report in Ghana [ 45 ]. Postulated mechanisms underlying HIV-HCV/HBV co-infections include HCV proliferation and the suppression of T helper cells [ 46 , 47 , 48 ], whereas HBV infection is associated with increased T-cell apoptosis [ 49 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar findings of negative immune recovery have been reported among HIV co-infected patients in other African countries [ 42 , 44 ]. However, the sustained increases in the CD4+ cell count among the HIV mono-infected is reflective of a positive immunological outcome to therapy, which is also consistent with a previous report in Ghana [ 45 ]. Postulated mechanisms underlying HIV-HCV/HBV co-infections include HCV proliferation and the suppression of T helper cells [ 46 , 47 , 48 ], whereas HBV infection is associated with increased T-cell apoptosis [ 49 ].…”
Section: Discussionsupporting
confidence: 91%
“…Postulated mechanisms underlying HIV-HCV/HBV co-infections include HCV proliferation and the suppression of T helper cells [ 46 , 47 , 48 ], whereas HBV infection is associated with increased T-cell apoptosis [ 49 ]. Moreover, the improvement in weight observed among the HIV mono-infected in our study was similarly demonstrated by Ohene and colleagues who found increases in weight levels after therapy was initiated [ 45 ].…”
Section: Discussionsupporting
confidence: 86%
“…This is an evidence of stigmatization as clients feel reluctant to pick up salvage dispensation or transferred to nearby facilities. This was similar to Lifson et al findings that identified travels and stigma in raising attrition 27 29 . The mental state of PLHIV and their relationship with care providers affected their consistency in care.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, 13.8/100PY in Thailand [ 8 ], 41.5/100PY in Swiss [ 9 ], 28.3/100PY in Brazil [ 10 ], 16.2/100PY in West Africa [ 11 ], 18.6/100PY in Kenya [ 12 ] and the proportion of regimen change in Ethiopia was 21.8 % [ 13 ]. Different studies revealed that baseline regimen [ 1 , 12 , 14 ], WHO stage [ 12 , 15 ], CD4 count [ 6 , 16 , 17 ] and patient weight [ 12 , 15 ] were some predictors of initial regimen change.…”
Section: Introductionmentioning
confidence: 99%